Children's Literature as a Learning Media in Improving Social Souls in Children - Nofita Sari (Educatio, 2020)
The Troublemaker novel which is included in the work of the children's satra gives an overview of the lives of children. The lives of children who at this time have been lost because of technological advances. The Troublemaker novel comes with a moral message about the importance of socializing and introducing children's world lives. Where the world of children is a world of play and be happy with their environment. The Troublemaker novel tells the story of a child who is from Australia and lives in the Pelikan Complex. With the arrival of a child who came from Australia, it made the pelicans have a different life than before. The results showed that the moral message contained in the troublemaker novel is moral about human relations with other humans in the social environment in the form of mutual respect, please help and care for one another. In today's life, through the moral message conveyed in the troublemaker novel is a moral that has been lost on children today. The figure of the main character named Luna can give a picture of the lives of children before getting to know technology. Where children today are more fond of playing mobile phones or the like than playing together with relatives.